PEDAGOGICAL AND PSYCHOLOGICAL FEATURES OF PREPARING CHILDREN FOR SCHOOL (Multidisciplinary Journal of Science and Technology, 2026)
This article provides a profound analysis of the pedagogical and psychological characteristics of the process of preparing children for school. The content of the concept of school readiness, its structural components, and aspects related to the level of children's individual development are highlighted.